Research on an Output Power Model of a Doubly-Fed Variable-Speed Pumped Storage Unit with Switching Process - Guopeng Zhao; Jiyun Ren (Applied Sciences, 2019)
The doubly-fed variable-speed pumped storage (DFVSPS) is an effective method to balance the fluctuation of renewable energy generation and is an important means of frequency and voltage regulation of a power grid. Firstly, this paper introduces the structure and mathematical model of the DFVSPS unit. Secondly, the control methods of each switching stage in generating mode and pump mode are proposed, and the simulation study of each stage of DFVSPS switching process is carried out by MATLAB/Simulink. Thirdly, when studying the regulating effect of DFVSPS unit in the power system, due to the high switching frequency of converter in the electromagnetic transient model, the simulation speed is very slow and the data volume is large, so the model of DFVSPS unit needs to be simplified. By analyzing the dynamic behavior of the pumped storage power station, the mathematical model of output power of the DFVSPS unit is established, which includes start-up stage, load ramping stage, stable operation stage, load rejection stage and shutdown stage of generating mode and pump mode. Finally, the simplified model of DFVSPS unit is applied to a simple power system to verify its regulating effect on grid power.